2018
DOI: 10.1186/s12920-018-0402-6
|View full text |Cite
|
Sign up to set email alerts
|

TAP: a targeted clinical genomics pipeline for detecting transcript variants using RNA-seq data

Abstract: BackgroundRNA-seq is a powerful and cost-effective technology for molecular diagnostics of cancer and other diseases, and it can reach its full potential when coupled with validated clinical-grade informatics tools. Despite recent advances in long-read sequencing, transcriptome assembly of short reads remains a useful and cost-effective methodology for unveiling transcript-level rearrangements and novel isoforms. One of the major concerns for adopting the proven de novo assembly approach for RNA-seq data in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…1A). The targeted assembly pipeline (TAP) (Chiu et al 2018) on the transcriptome showed the synonymous germline variant (c.996G>A, p.Ser332Ser) to create a novel canonical AG acceptor splice site removing 42 bp and 14 amino acids (Fig. 1B; Supplemental Table S2E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). The targeted assembly pipeline (TAP) (Chiu et al 2018) on the transcriptome showed the synonymous germline variant (c.996G>A, p.Ser332Ser) to create a novel canonical AG acceptor splice site removing 42 bp and 14 amino acids (Fig. 1B; Supplemental Table S2E).…”
Section: Resultsmentioning
confidence: 99%
“…The targeted assembly pipeline (TAP) (Chiu et al 2018) on the transcriptome showed two mechanisms of abnormal splicing associated with this germline variant. The first mechanism leads to a 9-bp deletion due to the canonical splice site acceptor disruption and selection of a downstream canonical AG acceptor splice site at Chr 1:45797750–45797751 (new exon start at Chr 1:45797749).…”
Section: Resultsmentioning
confidence: 99%
“…To detect inter- and intra-gene SVs, we performed de novo assembly on all the RNA-Seq libraries, using Trans-ABySS (version 1.5.2) 70 and PAVfinder (versions 0.2.0 and 0.3.0) 71 . PAVfinder relied on GMAP (version 2014-12-28) 58 and BWA MEM (version 0.7.12-r1039) 72 for contig-to-genome, contig-to-transcript, and read-to-contig alignments.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that a spaced seed approach may be superior in terms of overall specificity when using incomplete or missing reference sequences. The practical speed and favorable sensitivity of miBFs have prompted the use of BBT in the targeted transcriptome assembly pipeline called TAP (43) and may be a good fit for other pipelines performing read binning.…”
Section: Discussionmentioning
confidence: 99%